2022
DOI: 10.3389/fmicb.2022.944006
|View full text |Cite
|
Sign up to set email alerts
|

Locally generated C3 regulates the clearance of Toxoplasma gondii by IFN-γ-primed macrophage through regulation of xenophagy

Abstract: Exogenous pathogen infection can induce autophagy in cells. Autophagy is essential for cell survival, development, and homeostasis. It not only regulates cell defense and stress, but also has a close relationship with innate and adaptive immunity. Complement is an important part of innate immunity, which could be activated by three approaches, including classic, alternative, and lectin pathways. All the three pathways result in the activation of C3, and generate anaphylatoxin fragments C3a and C5a, and formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the present ox-LDL treated HUVEC models, it was found that the autophagic flux impairment of HUVECs occurred along with the upregulation of miR-483-5p, proposing the potential relationship between miR-483-5p and autophagy, as well as endothelial dysfunction. 3-methyladenine (3-MA) is a classical autophagy inhibitor, which mainly plays an inhibitory role in the formation and development of autophagosomes [ 40 ]. In the current study, the addition of 3-MA was applied to inhibit the HUVECs autophagy, in order to investigate the role of miR-483-5p in cell autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present ox-LDL treated HUVEC models, it was found that the autophagic flux impairment of HUVECs occurred along with the upregulation of miR-483-5p, proposing the potential relationship between miR-483-5p and autophagy, as well as endothelial dysfunction. 3-methyladenine (3-MA) is a classical autophagy inhibitor, which mainly plays an inhibitory role in the formation and development of autophagosomes [ 40 ]. In the current study, the addition of 3-MA was applied to inhibit the HUVECs autophagy, in order to investigate the role of miR-483-5p in cell autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…It was embedded in resin at 65 °C for 48 h. Then, the samples were cut into ultrathin sections and l loaded onto 300-mesh copper grids (Plano GmbH, Marburg, Germany), then stained with uranyl acetate and lead citrate. The grids were viewed under transmission electron microscopy (Hitachi, HT7800, Tokyo, Japan) [ 49 ].…”
Section: Methodsmentioning
confidence: 99%